Ektoparazitska entomofavna sesalcev (Mammalia) Jugoslavije. 1, Insektivori in na njih ugotovljeni sifonapteri - Brelih, Savo (Scopolia, 1978)
The authors are gicing data on 31 species and 14 subspecies of Siphonaptera onYugoslav Insectivora.The characteristics of Leptopsylla algira scopolii ssp.n. and of the as yet unknown female of the species Palaeopsylla smiti PEUS, 1965. For the territory of Yugoslavia the following new taxons are given: Hystrichopsylla talpae talpae (CURTIS, 1826), Rhadinopsylla ?sobrina PEUS, 1958, Palaeopsylla smiti PEUS, 1965, Ctenophthalmus bisoctodentatus heselhausi (OUDEMANS, 1914), Ct. congener troilus PEUS, 1954, Ct. assimilis bernhardus PEUS, 1965 and Leptopsylla algira scopolii ssp. n. Besides, the survey of the hosts and of the Siphonaptera stated on them is presented and soare some taconomical, zoogeographical and ecological observations.
Keywords: Žuželke; Yugoslavia; Jugoslavija; entomologija; ektoparaziti; bolhe; sesalci; voluharice